2020
DOI: 10.1111/hepr.13547
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of direct‐acting antiviral treatments for patients with hepatitis C after hepatocellular carcinoma are equivalent to interferon treatment

Abstract: It remains unclear how direct acting antiviral (DAA) treatments influence hepatocellular carcinoma (HCC) recurrence and survival in comparison with interferon (IFN). Methods: In total, 338 patients with chronic hepatitis C virus (HCV) infection and previous HCC treatments who initiated IFN (N=88, IFN group) or DAA treatment (N=250, DAA group) from January 2005 to November 2017 at 23 hospitals and achieved sustained virologic response (SVR) were analyzed. Cumulative HCC recurrence and survival rates were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
(75 reference statements)
0
15
0
Order By: Relevance
“…On the other hand, whether or not it contributes to the improvement of recurrence-free survival is debatable. Initially, the possibility of early recurrence after DAA treatment was suggested [ 36 , 37 ]; however, subsequent reports, including meta-analyses, have shown no difference in the risk of recurrence when compared to IFN treatment [ 38 41 ]. Although time bias cannot be excluded completely, a recent report showed that the recurrence rate was significantly lower in the group that achieved SVR by DAA treatment after HCC treatment compared with the untreated group [ 32 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, whether or not it contributes to the improvement of recurrence-free survival is debatable. Initially, the possibility of early recurrence after DAA treatment was suggested [ 36 , 37 ]; however, subsequent reports, including meta-analyses, have shown no difference in the risk of recurrence when compared to IFN treatment [ 38 41 ]. Although time bias cannot be excluded completely, a recent report showed that the recurrence rate was significantly lower in the group that achieved SVR by DAA treatment after HCC treatment compared with the untreated group [ 32 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus was defined according to the guidelines of the American Diabetes Association, 13 as in our previous report. 14 Patients with cirrhosis were defined as those who met one of the following criteria. Among the patients who underwent liver biopsy, patients with a METAVIR score of F4 were defined as having This study was performed in line with the ethics guidelines outlined in the Declaration of Helsinki and was approved by the institutional review boards of all participating hospitals (University Hospital Medical Information Network: 000015247, 000018561, 000020019, 000017703, 000025050, 000037575).…”
Section: Patientsmentioning
confidence: 99%
“…In a more recent international multicenter retrospective study published in 2020, there was no increase in the risk of HCC recurrence or the risk of mortality in patients with HCC waiting for liver transplantation[ 69 ]. Another group reported no difference in the behavior of HCC recurrence or mortality rates in patients who achieved SVR after either IFN or DAAs[ 70 ].…”
Section: Association Between Hcc Recurrence and Daasmentioning
confidence: 99%